Pengembangan Media Pembelajaran powerpoint interaktif berbasis inkuiri terbimbing pada Materi laju reaksi - Liza, Ranisa Eka (Journal of Technique Research (JTR), 2019)
The rate of reaction is one of the chemical materials studied in SMA / MA. This material is fact, concept, principle and procedural which must be explained by three levels of chemical representation. Based on the results of teacher interviews at SMAN 1 Ulakan Tapakis, SMAN 2 Sungai Limau and SMAN 14 Padang the teaching materials used have not yet presented submicroscopic levels. So that students don?t know the actual process that occurs in chemical reactions. One of the learning media that can visualize three levels of chemical representation is powerpoint media. Therefore the development of guided inquiry-based interactive powerpoint learning media was carried out on the reaction rate material and expressed its level of validity and practicality as a chemical learning media. The type of research conducted is the development of a 4-D model (define, design, develop and diseminate). Based on the results of data validity analysis, the average kappa moment was 0.85 with a very high validity category and the results of practical data obtained by the average kappa moment of 0.88 by teachers and 0.86 by students with very high practicality categories.